Prdm15 acts upstream of Wnt4 signaling in anterior neural development of Xenopus laevis - Saumweber, Ernestine; Mzoughi, Slim; Khadra, Arin; Werberger, Anja; Schumann, Sven; Guccione, Ernesto; Schmeisser, Michael J.; Kühl, Susanne J. (Frontiers in Cell and Developmental Biology, 2024)
Mutations in PRDM15 lead to a syndromic form of holoprosencephaly (HPE) known as Galloway-Mowat syndrome (GAMOS). While a connection between PRDM15, a zinc finger transcription factor, and WNT/PCP signaling has been established, there is a critical need to delve deeper into their contributions to early development and GAMOS pathogenesis. We used the South African clawed frog Xenopus laevis as vertebrate model organism and observed that prdm15 is enriched in tissues and organs affected in GAMOS. Furthermore, we generated a morpholino oligonucleotide-mediated prdm15 knockdown model showing that the depletion of Prdm15 leads to abnormal eye, head and brain development, effectively recapitulating the anterior neural features of GAMOS. Analysis of the underlying molecular basis revealed a reduced expression of key genes associated with eye, head and brain development. Notably, this reduction could be rescued by the introduction of wnt4 RNA, particularly during induction of the respective tissues. Mechanistically, our data demonstrates that Prdm15 acts upstream of both canonical and non-canonical Wnt4 signaling during anterior neural development. Our findings describe severe ocular and anterior neural abnormalities upon Prdm15 depletion and elucidate the role of Prdm15 in canonical and non-canonical Wnt4 signaling.